Integrated Information Dissemination System (IIDS) Annapurna Krishi Prasar Seva (AKPS) - Anurag, T. S.; Bhatia, V. K.; Ramaraju, G. V. (Indian Farming, 2015)
A prototype has been developed through outsourcing with the NAIP support called the Integrated Information Dissemination System for the service of the farmers. The system is connected to a centralized database which has all the information of the farm, farmer and previous transactions.